2017
DOI: 10.1063/1.4974334
|View full text |Cite
|
Sign up to set email alerts
|

Double threshold behavior in a resonance-controlled ZnO random laser

Abstract: We observed unusual lasing characteristics, such as double thresholds and blue-shift of lasing peak, in a resonance-controlled ZnO random laser. From the analysis of lasing threshold carrier density, we found that the lasing at 1st and 2nd thresholds possibly arises from different mechanisms; the lasing at 1st threshold involves exciton recombination, whereas the lasing at 2nd threshold is caused by electron-hole plasma recombination, which is the typical origin of conventional random lasers. These phenomena a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…On the other hand, we have been interested in random structures and their modal control for the practical applications such as light emitting devices, sensors, and light extracting/harvesting. For this purpose, several approaches for the control of random lasing modes had been proposed such as use of resonant scatterers [7][8][9][10][11], limiting excitation area [12,13], temperature control [14][15][16], tuning density of scatterers [17]. Among these approaches, it had been reported that changes in lasing modes were observed in random lasers fabricated on a soft substrate due to the structural changes induced by mechanically stretching the substrate [18][19][20], which has a merit of in situ tuning of lasing modes by adjusting the amount of bending or stretching the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, we have been interested in random structures and their modal control for the practical applications such as light emitting devices, sensors, and light extracting/harvesting. For this purpose, several approaches for the control of random lasing modes had been proposed such as use of resonant scatterers [7][8][9][10][11], limiting excitation area [12,13], temperature control [14][15][16], tuning density of scatterers [17]. Among these approaches, it had been reported that changes in lasing modes were observed in random lasers fabricated on a soft substrate due to the structural changes induced by mechanically stretching the substrate [18][19][20], which has a merit of in situ tuning of lasing modes by adjusting the amount of bending or stretching the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…So far, only one or two out of these three lasing regimes have been reported for a given structure, independently of the material system examined [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] . Thresholds for the onset of photon lasing involving excitons have been reported as two orders of magnitude 11,12,16,18 or a factor two 19,20 greater with respect to that of polariton type.…”
mentioning
confidence: 99%
“…Thresholds for the onset of photon lasing involving excitons have been reported as two orders of magnitude 11,12,16,18 or a factor two 19,20 greater with respect to that of polariton type. The transition from photon lasing involving excitons to photon lasing involving an e-h plasma has been evidenced only recently in the emission from ZnO-based microcavity 27 . This shows that the actual relation between all three lasing regimes has still not been established.…”
mentioning
confidence: 99%
“…Random lasing [10] has been claimed to be fundamentally incompatible with polaritons. From recent research developments however it turns out that it is not yet clear whether random lasers are either pure photon lasers or pure polariton lasers, or whether they even have both characteristics at the same time [11]. Thresholds like in conventional lasers may be observed [12,13].…”
Section: Introductionmentioning
confidence: 99%